Integrating resilience with urban sustainability in neglected neighborhoods: Challenges and opportunities of transitioning to decentralized water management in Mexico City. (August 2015) - Chelleri, L.; Schuetze, T.; Salvati, L.
Abstract: The impacts of climate change and decreasing local resources are increasingly threatening the resilience and sustainable management of urban areas and infrastructures worldwide. To cope with such threads and vulnerabilities, urban sustainability and resilience oriented plans have been developed. Accordingly, policy makers need to learn how to properly integrate urban sustainability with urban resilience principles and practices in the re-shaping of urban agendas. In order to highlight the future potential of integrating transformative resilience principles into the general sustainability approach, this paper provides a critical review of a recent and successful urban regeneration and development plan, the "Mexico City Green Plan". This paper also discusses a feasibility study for urban redevelopment and transition towards resilience in Mexico City, in order to illustrate the necessity and potential of urban resilience for the improvement of the life prospects of disadvantaged inhabitant groups. The Valle del Chalco neighborhood in Mexico City is presented as an example, whereby resilient and sustainable urban transformation was achieved through an integrated and sustainable decentralized water management and infrastructure plan. In practice, the terms 'Sustainability' and 'Resilience' can be exploited to justify conventional, non-sustainable urban development practices. The results discussed in this paper demonstrate the necessity of the integration of transformative resilience principles within sustainable urban redevelopment and regeneration. The main findings are i) Policy makers underestimate the potential of urban resilience in shaping more sustainable urban futures, since they only understand resilience as the flipside of specific vulnerabilities, ii) The building of urban resilience within sustainable urban transitions and redevelopment can effectively foster people empowerment, particularly in combination with the decentralization of resources management systems, and iii) The main challenge for the implementation and execution of transitions processes towards urban resilience and sustainability is the elimination of political barriers. Highlights: Urban resilience is not only the flip-side of specific vulnerabilities. Urban resilience should be aligned within urban sustainability agenda and goals. Transformational resilience can foster people empowerment and quality of life. The main barriers to this are political, not technical.